The walking dead. Vol. 13, Too far gone - Kirkman, Robert (Kirkman, Robert. Walking dead., 2010)
Rick is on edge despite the fact that life in the community is as near to normal as the group can ever hope it to be, and some fear that his anxiety will be the group's downfall.